(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2019)
All photons will burn you. How do we describe photons as having different amounts of energy? This paper illustrates photons do not have different amounts of energies, rather different types of energy. The experiment of 1800 provides enough data to be analyzed because it has that third point to question the idea that photons carry different amounts of energy. This paper argues that all photons have equal amounts of energy just different types of energy. The composition of the energy within a photon depends on the frequency of a photon, a lower frequency photon like those represented by infrared can boil water faster than higher frequency blue light. A higher frequency photon like a gamma particle is stopped by lead. Given the nature that heat is from photons we can start thinking of sophisticated thermometers that give us the quality of heat not just the quantity of heat. It is the atmosphere that gives more evidence around the nature of photons, we can understand the cycle of the photon/ photonic cycle/ electromagnetic cycle, allowing us to ponder on deep philosophical meanings, intelligent life is there for universe to sustain itself, as well as ask the question why we are not burning given the nature of low frequency electromagnetic radiation. And for those vigorously looking for habitable planets out there, the idea of the circumstellar habitable zone must change to accommodate the proper understanding of heat.